Children and Women's Participation Dynamics: Transitory and Long-Term Effects - Alexandru Voicu; Hielke Buddelmeyer (Institute for the Study of Labor (IZA), 2003)
Children affect the after-birth labor force participation of women in two ways. Directly, the time spent in child-care reduces the labor market effort. The time spent out of the labor market while on maternity leave alters women's participation experience and, thus, indirectly affects subsequent participation behavior. This paper proposes a model that disentangles the direct and indirect effect of children on women's labor force participation, and evaluates their relative importance. Participation decisions on a three-state space - employed full-time, employed part-time, not employed - are represented by a multivariate probit model with a general correlation structure. The model allows for a high degree of flexibility in modeling the dependence of sequential decisions. The estimation is performed using Markov chain Monte Carlo methods. It is shown that the indirect effect, through time out of the labor market, is more important. The discrepancy is sharper for full-time employment and grows with the length of the interruption.
Keywords: C15; J13; C11; J22; 330; female labor supply; multivariate probit model; Gibbs sampler; Frauenerwerbstätigkeit; Arbeitsangebot; Kinderbetreuung; Kinder; Schätzung; Deutschland